2015
DOI: 10.1016/j.homp.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

DNA fragmentation and cell cycle arrest: a hallmark of apoptosis induced by Ruta graveolens in human colon cancer cells

Abstract: In the present study, we investigated the anti-cancer effect of various potencies of Ruta graveolens (Ruta) on COLO-205 cell line, as evidenced by cytotoxicity, migration, clonogenecity, morphological and biochemical changes and modification in the levels of genes associated with apoptosis and cell cycle. On treatment of COLO-205 cells maximal effects were seen with mother tincture (MT) and 30C potencies, wherein decrease in cell viability along with reduced clonogenecity and migration capabilities were noted.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 31 publications
1
36
0
1
Order By: Relevance
“…Phyto MT showed intermediate cytotoxicity to HeLa cervical cancer cells and PC3 prostate cancer cells [18]. Consistent with the above, down-regulation of Bcl-2 and Akt (the gene for protein kinase B), and upregulation of p53 and Bax also occurred [17,18]. In vitro, by Student paired t test and one-way ANOVA, Lycopodium clavatum (running clubmoss) 5C and 15C are dose dependently selectively cytotoxic to HeLa cells (p<0.001), and spare PBMC [19].…”
Section: Homeopathic Cancer Treatmentssupporting
confidence: 78%
See 1 more Smart Citation
“…Phyto MT showed intermediate cytotoxicity to HeLa cervical cancer cells and PC3 prostate cancer cells [18]. Consistent with the above, down-regulation of Bcl-2 and Akt (the gene for protein kinase B), and upregulation of p53 and Bax also occurred [17,18]. In vitro, by Student paired t test and one-way ANOVA, Lycopodium clavatum (running clubmoss) 5C and 15C are dose dependently selectively cytotoxic to HeLa cells (p<0.001), and spare PBMC [19].…”
Section: Homeopathic Cancer Treatmentssupporting
confidence: 78%
“…Sars had a maximum cytotoxicity of 22.1% against MDCK normal kidney epithelial cell line [4]. Ruta is associated with down-regulation of B-cell lymphoma 2 (Bcl-2), upregulation of caspases-3 and -9, Bcl-2-associated X (Bax), p21 and p27 expression leading to intrinsic apoptosis and G2/M cell cycle checkpoint arrest [17]. Ruta has shown selective cytotoxicity to Glioblastoma multiforme while sparing normal peripheral blood lymphocytes (PBMC) [3].…”
Section: Homeopathic Cancer Treatmentsmentioning
confidence: 99%
“…At higher concentrations genistein caused persistent cell cycle arrest at G2/M phase (Pagliacci et al, 1994). Another plant product "Ruta" showed anticancer activity against colon cancer cell line COLO 205 and it caused cell death and cell cycle arrest at G2/M phase (Arora and Tandon, 2015). The cytotoxic and anti-clonogenic effects of ICL extracts on SCC-9 cells were further examined by evaluating the cell cycle distribution post treatment.Data from the present study showed that the ICL extracts from the plantI.…”
Section: Discussionmentioning
confidence: 99%
“…Integrity of DNA is a prerequisite for the survival and for the maintenance of infinite proliferative potential of cancer cells and many phytocompounds with anticancer property disrupt this integrity (Tsai et al, 2012;Arora and Tandon, 2015). Presence of a characteristic DNA ladder in the cancer cells post anticancer treatment is a hallmark of apoptotic cell death (Wyllie, 1980;Hengartner, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The optical density (OD) was measured at 630 nm using Absorbance Reader BioTek ELx800 (BioTek Instruments, Inc., Winooski, Vermont, USA). The percentage of DNA fragmentation was calculated as {OD tube B/(OD tube A + OD tube B)×100%} [11].…”
Section: Methodsmentioning
confidence: 99%